The Image Of Ummat Party In The 2024 General Election - Bakran Suni (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
This study will examine the Bandung Regency Ummat Party's political communication and image as a new party ahead of the 2024 election. The research strategy employed was a literature review and in-depth interviews with numerous connected sources. The data analysis approach draws findings using data triangulation procedures, specifically the data collection, reduction, and presentation stages. The data supplied is then tailored to the researcher's requirements for studying the research challenge. The study's findings indicate that the Bandung Regency Ummat Party is attempting to project a new identity that differs from its prior identity. The Ummat Party attempts to establish its political image through the use of mass media as well as the character and stature of party officials. According to the findings of this study, the Bandung Regency Ummat Party promotes social media operations in order to improve its political image. The Ummat Party realizes that, as a new party, identity and image are vital in attracting public interest and publicly introducing the party.